2003
DOI: 10.1097/01.ju.0000046780.23389.e0
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Genistein During Gestation and Lactation Demasculinizes the Reproductive System in Rats

Abstract: Perinatal genistein exposure results in transient and lasting alterations in masculinization of the reproductive system. These results extend our knowledge of the effects of early genistein exposure on male development and may have implications for human health in terms of potential relationships of endocrine disrupters and urogenital abnormalities thought to be increasing in incidence in boys and men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
4
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 18 publications
8
93
4
14
Order By: Relevance
“…Although the maximum dose in the present study was higher than that of these studies, no abnormal endocrine-mediated findings were detected in the present pups. In addition, prepubertal urogenital abnormalities, smaller male anogenital distances and testis size, and delayed preputial separation were detected in pups born to dams given genistein at doses of 5 and 300 mg/kg/day throughout gestation and lactation under a phytoestrogen-free diet [17]. The difference between our study and these previous studies lay in whether a diet containing phytoestrogens was given to dams from early stages of their life.…”
contrasting
confidence: 70%
“…Although the maximum dose in the present study was higher than that of these studies, no abnormal endocrine-mediated findings were detected in the present pups. In addition, prepubertal urogenital abnormalities, smaller male anogenital distances and testis size, and delayed preputial separation were detected in pups born to dams given genistein at doses of 5 and 300 mg/kg/day throughout gestation and lactation under a phytoestrogen-free diet [17]. The difference between our study and these previous studies lay in whether a diet containing phytoestrogens was given to dams from early stages of their life.…”
contrasting
confidence: 70%
“…In past decades, most studies showed that phytoestrogens given in high dose or at critical stages of development in rodents can result in severe reproductive system disorders, such as inhibition of LH secretion, decrease of plasma testosterone concentrations and prostate weight (Wanichacheewa et al, 2001;Wisniewski et al, 2003;Opalka et al, 2004). Simultaneously, some authors reported that there are no significant effects of phytoestrogens in rodents (Roberts et al, 2000;Mitchell et al, 2001;Lamartiniere et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, exposure to isoflavone during gestation and lactation (dietary exposure) or perinatally (oral gavage) yielded, once again, inconsistent results. While some reports found no reproductive defects (Fielden et al, 2003;Kang et al, 2002;Nagao et al, 2001), others reported variable persistent phenotypic and behavioral reproductive abnormalities such as decreased testicular weight or size (Atanassova et al, 2000;West et al, 2005;Wisniewski et al, 2003), decreased spermatogenesis (Atanassova et al, 2000;West et al, 2005), lower FSH (Atanassova et al, 2000) and testosterone levels (Wisniewski et al, 2003), smaller ano-genital distance (Wisniewski et al, 2003(Wisniewski et al, , 2005 and alterations of reproductive and aggressive behavior (Wisniewski et al, 2003(Wisniewski et al, , 2005.…”
Section: Soy Phytoestrogens and Male Reproductive Functionmentioning
confidence: 99%